Pengembangan Buku Dongeng Berbasis Sainsmatika untuk Meningkatkan Kemampuan Berpikir Kreatif dan Karakter Bersahabat - Agnestasia Ramadhani Putri; Ali Mustadi (SEJ (Science Education Journal), 2018)
This research aims to develop an instructional material to improve students' creative thinking and friendliness. This study was developmental research applying the R&D model of Borg & Gall. The subjects were 124 fourth grade students in Yogyakarta Special Region, Gunungkidul. The data collected through interviews, tests, observations, and questionnaires. The appropriateness of the sainsmatika-based fairy tale book was ana- lyzed qualitatively and the effectiveness of it analyzed using a one-way MANOVA test at the significance level of 5%. The findings were as follows: (1) the appropriateness of the sainsmatika-based story tale book gets good category scores for the mathematical content aspect and very good category scores for the science content, media and lan- guage aspect also get very good category score from student-teacher responses. (2) The score of the effectiveness test using one-way MANOVA is 0,000<0.05. Therefore, sainsmatika-based story tale book is able to improve students' creative thinking skills and friendliness.